Morphological characterization of unique genotypes of nutmeg (Myristica fragrans Houtt.) - Priyanka, S. C.; Miniraj, N. (Journal of Tropical Agriculture, 2017)
Twenty one unique accessions of nutmeg possessing 13 distinct characters were identified and collected through an extensive survey carried out in the nutmeg growing tracts of Kerala. These unique genotypes along with the two improved accessions were subjected to morphological characterization. As a deviation from the normal nutmeg, some unique types such as yellow maced nutmeg, double seeded nutmeg, cluster fruited nutmeg, monoecious, wild and grape nutmegs were identified in the study. All these accessions were characterized using seven qualitative and fourteen quantitative traits. Twenty three accessions were grouped into 12 clusters at 60% similarity. A concept diagram was developed for utilizing these unique accessions. Yellow maced accessions (YL-1 and YL-2) can be directly utilized for yellow colour, as they fetch premium price in the market. Double seeded accession (DS-1) had the highest dry nut weight and kernel weight. Seedless nutmeg accession (SL-1) possessed highest fresh mace weight. Wild nutmeg (M. malabarica) possessed fruits which were large, having brown velvety rind with yellowish orange coloured mace. Cluster fruited accession (CF-1) was the best accession among all the unique nutmeg accessions, possessing all the desirable features of an elite nutmeg genotype. All the unique accessions are worthy of conservation.